2016
DOI: 10.1002/hbm.23185
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory activation in fronto-parietal cortices among HIV-infected persons during a monetary decision-making task

Abstract: HIV infection can cause direct and indirect damage to the brain and is consistently associated with neurocognitive disorders, including impairments in decision-making capacities. The tendency to devalue rewards that are delayed (temporal discounting) is relevant to a range of health risk behaviors. Making choices about delayed rewards engages the executive control network of the brain, which has been found to be affected by HIV. In this case-control study of 18 HIV-positive and 17 HIV-negative adults, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 85 publications
(107 reference statements)
3
19
0
Order By: Relevance
“…For example, Plessis et al (2015) found that HIV was associated with hypoactivation in the ventral striatum during a task involving reward anticipation and reward outcome. Consistent with compensation theory (Barulli and Stern, 2013), two recent studies have shown that HIV-positive participants exhibit greater activation on easier tasks, but lesser activation as the task becomes more difficult (Caldwell et al, 2014; Meade et al, 2016). In another fMRI study that examined decision making in the context of uncertainty, HIV-positive individuals had greater activation than HIV-negative individuals in the ACC, DLPFC, basal ganglia, and thalamus when choosing risky gambles, but lesser activation in the ACC and DLPFC when choosing safe gambles (Connolly et al, 2014).…”
Section: Discussionmentioning
confidence: 75%
“…For example, Plessis et al (2015) found that HIV was associated with hypoactivation in the ventral striatum during a task involving reward anticipation and reward outcome. Consistent with compensation theory (Barulli and Stern, 2013), two recent studies have shown that HIV-positive participants exhibit greater activation on easier tasks, but lesser activation as the task becomes more difficult (Caldwell et al, 2014; Meade et al, 2016). In another fMRI study that examined decision making in the context of uncertainty, HIV-positive individuals had greater activation than HIV-negative individuals in the ACC, DLPFC, basal ganglia, and thalamus when choosing risky gambles, but lesser activation in the ACC and DLPFC when choosing safe gambles (Connolly et al, 2014).…”
Section: Discussionmentioning
confidence: 75%
“…The hypothesized result of this breakdown in network segregation is increased neural activity in less efficient neural clusters (Fornito and Bullmore, 2015). Indeed, multiple neuroimaging studies of cognitive function in HIV have found increased neural activation during executive function tasks despite comparable behavioral performance relative to HIV-negative individuals (Meade et al, 2016; Plessis et al, 2015). Lower clustering coefficient was also associated with lower nadir CD4 cell count.…”
Section: Discussionmentioning
confidence: 99%
“…Decision-making under ambiguity, when risk and reward contingencies are not explicitly known, appears to be particularly impaired among HIV+ individuals compared to decision-making under specified conditions (Brand, Grabenhorst, Starcke, Vandekerckhove, & Markowitsch, 2007; Martin et al, 2016; Martin et al, 2013). Functional imaging studies suggest that HIV infection is associated with abnormal activation in several brain regions known to support decision-making processes, including the medial PFC, the dorsal striatum, the ventral striatum, and the insula (Connolly et al, 2014; Meade et al, 2016). In agreement with our findings demonstrating a relationship between current immunologic status and decision-making ability, lower current CD4 cell count has been associated with greater activation of prefrontal brain regions during a decision-making task (Connolly et al, 2014).…”
Section: Discussionmentioning
confidence: 99%